MEDICINAL USES OF MUSHROOMS IN NIGERIA: TOWARDS FULL AND SUSTAINABLE EXPLOITATION. - Oyetayo, Olusegun V. (African Journal of Traditional, Complementary and Alternative Medicines, 2011)
For centuries, mushrooms have been appreciated as sources of food nutrients and pharmacologically important compounds useful in medicine. Yet not all the medicinal properties of mushrooms have been exploited. The above statement is more pertinent to mushrooms that are indigenous to Nigeria. There are inadequate data on the identity and medicinal properties of these wild mushrooms. Information on the ethnomedicinal uses of some mushrooms such as Pleurotus tuber-regium used for headache, stomach pain fever, cold, constipation; Lentinus squarullosus for mumps, heart diseases; Termitomyces microcarpus for gonorrhea; Calvatia cyathiformis for leucorrhea, barreness; Ganoderma lucidum for treating arthritis, neoplasia; G. resinaceum used for hyperglycemia, liver diseases (hepatoprotector); G. applanatum used as antioxidant and for diabetes had been gathered through survey. The above information is mostly obtained from traditional herbalists who in most cases will not disclose their preparation compositions. A lot of these mushrooms are obtained only in the wild. Scientific documents of the identities and medicinal properties are still scanty. Preliminary studies on some species of Temitomyces, Lenzites and Lentinus species showed that they possess appreciable antimicrobial and antioxidant properties. Moreover, molecular characterization also reveals that they are not 100% homologous with existing sequences under the same name in GenBank. It is therefore pertinent that well structured studies on their ecology, identification and medicinal uses be carried out. This will make the full exploitation of the medicinal potentials of mushrooms indigenous to Nigeria realizable.